Preparing teachers to teach the STEM disciplines in America's urban schools - Craig, Cheryl J.; Evans, Paige K.; Stokes, Donna W. (Advances in research on teaching, 2021)
Bridging a gap in the literature by offering a comprehensive look at how STEM teacher education programs evolve over time, this book explores teachHOUSTON, a designer teacher education program created to respond to the lack of adequately prepared STEM teachers in Houston and the emerging urban school districts that surround it. Providing a systematic investigation of how prospective STEM educators are cultivated to be subject matter specialists and culturally relevant teachers, the authors of this volume delve into the academic, professional and personal perspectives of teacher experiences to emphasise the impact on prospective and unfurling teaching careers. The topics include the influence of parents, teachers and professors on educator development and how internships function as a form of professional development, in addition to the influence of National Science Foundation-funded STEM scholarships on the careers and lives of the teachHOUSTON graduates. Because STEM education is vital to human and economic prosperity, this volume is of interest to both national and international readers.